POVERTY IN THE SERIBU ARCHIPELAGO, INDONESIA: IS SINGLE-DIMENSIONAL POVERTY MEASUREMENT ENOUGH? - Andi Pitono; Adfin rochmad Baidhowah; Irawati Tamara (ipdn, 2025)
How much does the difference between various poverty measurements? Though has been discussed in the academic literature, that question has never been analysed empirically. To provide the empirical evidence, this paper conducted a survey in the Seribu Archipelago, Indonesia, on the monetary single-dimensional poverty, the monetary multi-dimensional poverty, and nonmonetary poverty with 636 sample. Providing survey of three poverty measurements, this analysis found that there was significant difference on the number of people categorised as the poor. Because this survey result supports theoretical understanding of broader issues of the poverty and government policy, this paper recommends the construction of comprehensive poverty measurement, not just relying on the monetary single-dimensional approach.